Impact of El Niño–Southern Oscillation and Mechanical Pruning Strategies on the Productivity, Alternate Bearing, and Vegetative Growth of Olive Hedgerows - Calvo, Franco; Calahorra, Maria Andrea; Trentacoste, Eduardo Rafael (MDPI, 2025)
Mechanical pruning in narrow olive hedgerows is essential for managing alternate bearing and facilitating mechanical harvesting by influencing the number of fruit load points. In olive cv. Arbequina hedgerows (2000 trees ha−1), two pruning times (winter and spring) and two pruning types (unilateral and bilateral) were applied under contrasting bearing conditions (ON and OFF seasons) over four consecutive seasons in La Rioja, Argentina. A strong El Niño–Southern Oscillation (ENSO) event during the final season had a profound impact, increasing winter temperatures by 2 °C and reducing the average chill accumulation by 23%, significantly reducing productivity and exacerbating alternate bearing. The results demonstrated that pruning timing alone was ineffective in controlling alternate bearing, while bilateral pruning during ON seasons showed promise in regularizing fruit and oil yields and enhancing water use efficiency. However, the severe effects of the ENSO, which disrupted the winter dormancy break of fruiting buds, could not be mitigated by the evaluated pruning strategies.